(untitled) (London Journal of Research In Humanities and Social Sciences, 2024)
The past school year 2019-2020 has experienced a situation of school confinement, which forced the observance of an online education, with certain repercussions: affectation on students who had been dragging some previous difficulty (OEI), impossibility of access to technological tools for daily educational performance, uncertainty about when and how the return to normality should take place, i.e., return to face-to-face. This caused teachers to express not only uncertainty in the exercise of their teaching, but also to see themselves jaded by changes that have not served to improve their professional situation, requiring sacrifices on a personal level. A study carried out aimed at analyzing the particular educational situation in the Autonomous Community of Galicia (Spain), has revealed the weariness of the teaching class, with complete independence of the type of school to which they are attached: public, private or concerted. The need to carry out various sampling-participation processes, to obtain the sample required by the study, given its relevance, was what motivated the analysis of what leads the group of teachers not to participate, determining, through an indicator, the degree of boredom with them.